Autonomous driveline system for electric vehicle - Rahman, Mohammed Ataur; Ihsan, Sany Izan; Darsivan, Fadly Jashi (Springer, 2026)
This is a comprehensive book on the development of autonomous driveline for electric and autonomous vehicle, which focuses on technological details, mathematical relationships, and basic design principles in line with the development of green transportation systems. It addresses topics that focus on the development of electric and autonomous vehicle driveline, such as artificial intelligent control energy system; intelligent battery thermal management system; autonomous two-speed transmission; intelligent electromagnetic continuously variable transmission. This book's good blend of theoretical review and technical design makes it an excellent platform for educating today's engineers, postgraduate students, and industries personnel.